BIOACTIVITY AND IN-SILICO ANALYSIS OF R-ALPINE BORANE PRODUCED BY STREPTOMYCES TOXYTRICINI JAR4 - JAYANTHI ABRAHAM,; RITIKA CHAUHAN, (International Journal of Pharma and Bio Sciences, 2015)
The present work deals with isolation, identification of bioactive metabolite produced by Streptomyces toxytricini JAR4 for various biological activities. The bioactive metabolite (1s,5s)-9-(2,6,6-trimethylbicyclo[3.1.1]heptan-3-yl)-9-borabicyclo[3.3.1]nonane produced by the strain JAR4 was obtained from the optimized culture medium through solvent extraction and molecular weight of the metabolite was characterized through Gas-chromatography mass spectrometry. The active constituents obtained after extraction and partial purification from the isolate JAR4 was tested against clinical pathogens and it was found to be efficiently inhibiting Pseudomonas aeruginosa, Salmonella sp., Staphylococcus aureus and Klebsiella pnuemoniae among various gram positive and gram negative pathogens. The in silico studies of the isolated bioactive compound reveal the binding with glutamine 6-phosphate synthase at active binding site when compared with standard antibiotic anticapsin through molecular docking performed by Autodock vina. Actinomycetes are the prolific source of antimicrobial metabolites therefore the present investigation reveals in vitro as well as in silico antimicrobial potential of terrestrial actinomycetes JAR4 against medically important clinical pathogens.